Analysis of hospital costs and insurance reimbursement systems for pneumonia patients: A literature review - Nopriyan Pujokusuma; Muhammad Syamsu Hidayat; Rochana Ruliyandari (Science Midwifery, 2026)
Pneumonia has remained one of the leading causes of global morbidity and mortality and has imposed a substantial clinical and financial burden on healthcare systems. The high cost of pneumonia care was influenced by disease severity, comorbidities, length of hospital stay, and the use of therapeutic and diagnostic interventions. The implementation of prospective payment systems, such as Diagnosis Related Groups (DRGs) and INA-CBG’s, aimed to improve cost efficiency; however, it often resulted in gaps between actual hospital costs and reimbursement tariffs. This literature review aimed to analyze hospital costs and insurance reimbursement systems for pneumonia patients. A Systematic Literature Review was conducted following PRISMA guidelines through searches of PubMed and Google Scholar for publications from 2020 to 2025. Eleven articles met the inclusion criteria and were analyzed narratively. The findings indicated that length of stay, clinical complexity, and the use of broad-spectrum antibiotics were the main determinants of high costs. Package-based payment systems improved efficiency but continued to face underfunding challenges. This study concluded that optimizing pneumonia cost management required clinical efficiency, accurate claims coding, and technological support to ensure hospital financial sustainability.